A noble metal / carbon nanosheet composite material and preparation method thereof

Preparation of precious metal/carbon nanosheet composite materials by pyrolysis of precious metal salts, polyvinylpyrrolidone and urea, solving the problems of wide particle size distribution, easy shedding and environmental pollution of precious metal catalysts in the prior art, achieving high activity and high stability Preparation of precious metal catalysts with high loading capacity, suitable for catalyst applications of a variety of precious metals.

CN114570359BActive Publication Date: 2024-12-20ZHOUKOU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111617554.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2024-12-20
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

The preparation method of precious metal catalysts in the prior art has problems such as wide distribution of precious metal nanoparticles, easy to fall off, environmental pollution and low utilization rate of raw materials, making it difficult to develop high activity, high stability and environmentally friendly precious metal catalysts.

Method used

The noble metal/carbon nanosheet composite material is prepared by mixing precious metal salts, polyvinylpyrrolidone and urea and heating at 160-240°C to form a precursor, and then heating to 800-1000°C under the protection of non-oxidizing gas to pyrolyze it, thereby achieving a pyrolysis of precious metal/carbon nanosheet composite material. Complete conversion and high loading of precious metal salts.

Benefits of technology

This method achieves a 100% conversion rate of precious metal salts, avoiding waste of precious metal raw materials, and the prepared precious metal/carbon nanosheet composite materials have high loading, stability and environmentally friendly characteristics, and are suitable for the preparation of a variety of precious metal catalysts. Extend the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114570359B_ABST
    Figure CN114570359B_ABST
Patent Text Reader

Abstract

The invention discloses a noble metal / carbon nanosheet composite material and a preparation method thereof, wherein noble metal salt, polyvinyl pyrrolidone and urea are uniformly mixed in a certain proportion, and then polymerized by heating at 160-240°C to completely form a solid state, and then cooled to room temperature to obtain a precursor, and then the obtained precursor is heated to 800-1000°C for pyrolysis under program temperature control and non-oxidizing gas protection, and naturally cooled to room temperature to obtain a noble metal / carbon nanosheet composite material, wherein the metal content can reach 40wt%, and the noble metal salt includes platinum salt, palladium salt, rhodium salt, ruthenium salt and iridium salt. The technical problems of incomplete conversion of noble metal raw materials and easy falling off of noble metals in the preparation process of noble metal catalysts are solved, and dual-element or multi-element noble metal composite materials can be prepared at the same time, and the product does not need pickling, is environmentally friendly, has a simple preparation process, and is conducive to industrialized amplification production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a noble metal / carbon nanosheet composite material and a preparation method thereof. Background Art

[0002] Precious metal catalysts are widely used in pharmaceutical synthesis, chemical production, energy catalysis and other fields due to their excellent catalytic activity and selectivity. Since precious metals have small reserves in the earth's crust and are expensive, it is crucial to improve the utilization rate of precious metals and develop highly active and stable precious metal catalysts.

[0003] In the prior art, the traditional impregnation method is used to prepare carbon-supported precious metal nanomaterials. After the precious metal salt solution is fully mixed with the activated carbon base, it is dried and reduced at high temperature to prepare the carbon-supported precious metal catalyst. The particle size distribution of the precious metal nanoparticles in the precious metal catalyst material prepared by this method is relatively wide. At the same time, the precious metal nanoparticles are easy to fall off during use, resulting in reduced catalyst activity. Patent CN111129511A proposes a method for preparing a nitrogen-doped carbon-supported platinum-based catalyst, which is to prepare a nitrogen-doped carbon carrier by polymer fibers obtained by high-temperature pyrolysis electrostatic spinning, and then grow platinum nanoparticles on the nitrogen-doped carbon carrier by liquid phase reduction. The platinum loading in the obtained catalyst material is large, but the preparation process is complicated, and highly toxic reducing agents and solvents such as sodium borohydride and N,N-dimethylformamide are used at the same time, which has great environmental hazards. Patent CN106916110A proposes a method for preparing a supported precious metal nanoparticle composite material, which uses a metal organic framework compound (ZIF-67) as a carrier and obtains a ZIF-67 supported precious metal nanocomposite material by an in-situ reduction method. The precious metal composite material obtained by this method has the advantages of small precious metal particle size and narrow particle size distribution, but the preparation cost of the metal organic framework compound is high. Toxic reducing agents such as sodium borohydride or hydrazine hydrate are used to obtain precious metal nanoparticles. At the same time, the precious metal salt is not fully reduced, resulting in waste of precious metal raw materials. Patent CN109569686A grows precious metal nanoparticles on primary amine modified activated carbon carrier by ultraviolet light reduction. The invention uses light ring primary to avoid the use of reducing agents such as sodium borohydride, which is environmentally friendly, but the light reduction method has the problem of insufficient reduction of precious metal salt raw materials and low raw material utilization.

[0004] Therefore, improving the conversion rate of precious metal salts and the stability of precious metal composite materials, and developing environmentally friendly preparation methods to prepare high-quality precious metal catalysts are important research and development directions in this technical field. Summary of the invention

[0005] In view of the above problems and technical deficiencies, the purpose of the present invention is to provide a method for preparing a precious metal / carbon nanosheet composite material, which is obtained by uniformly mixing precious metal salts, polyvinyl pyrrolidone and urea, heating them to 800-1000°C at a temperature of 160-240°C under a non-oxidizing gas, and gradually pyrolyzing them. The method is environmentally friendly and has a high metal conversion rate.

[0006] The technical solution is:

[0007] A method for preparing a noble metal / carbon nanosheet composite material, comprising the following steps:

[0008] (1) mixing a noble metal salt, polyvinyl pyrrolidone and urea in a certain proportion, heating and polymerizing at 160-240° C. until the mixture is completely solid, and then naturally cooling to room temperature to obtain a precursor;

[0009] (2) heating the precursor obtained in step (1) to 800-1000° C. under programmed temperature control and non-oxidizing gas protection, and then naturally cooling to room temperature to obtain a noble metal / carbon nanosheet composite material;

[0010] Furthermore, the noble metal salt in step (1) is a platinum salt, a palladium salt, an iridium salt, a ruthenium salt or a rhodium salt.

[0011] Furthermore, the noble metal salt used in step (1) is one or more of noble metal acid salts, noble metal chlorides, noble metal nitrates, and noble metal acetylacetonate compounds.

[0012] Furthermore, the noble metal salt used in step (1) is one or more of chloroplatinic acid, platinum tetrachloride, platinum dichloride, platinum acetylacetonate, and platinum nitrate.

[0013] Furthermore, in step (1), the mass ratio of polyvinyl pyrrolidone to urea is 1:4-1:30, and the molar amount of the monomer in polyvinyl pyrrolidone is more than 4 times that of the noble metal salt.

[0014] Furthermore, the heating time in step (1) is 2-6 hours, the programmed heating rate in step (2) is 1-10°C / min; and the pyrolysis time is 1-4 hours.

[0015] Furthermore, the non-oxidizing gas used in step (2) is one or a mixed gas of hydrogen, nitrogen, argon and helium.

[0016] Furthermore, the precious metal salt used in step (1) is one or more of chloroplatinic acid, platinum tetrachloride, platinum dichloride, platinum acetylacetonate, platinum nitrate, palladium chloride, palladium nitrate, palladium acetylacetonate, iridium trichloride, chloroiridic acid, iridium acetylacetonate, ruthenium trichloride, rhodium trichloride, and rhodium acetylacetonate.

[0017] Preferably, the heating temperature in step (1) is 200-220°C.

[0018] Preferably, the programmed heating rate in step (2) is 3-5°C / min.

[0019] Preferably, the pyrolysis time in step (2) is 2 hours.

[0020] Preferably, the non-oxidizing gas in step (2) is nitrogen.

[0021] Preferably, in step (1), the molar amount of the monomer in the polyvinyl pyrrolidone is 8-20 times that of the noble metal salt.

[0022] Preferably, in step (1), the mass ratio of polyvinyl pyrrolidone to urea is 1:5-1:20.

[0023] The noble metal / carbon nanosheet composite material is prepared according to the above method.

[0024] Due to the adoption of the above technical solution, the present invention has the following advantages compared with the prior art:

[0025] (1) The method for preparing the noble metal / carbon nanosheet composite material of the present invention is applicable to the preparation of a variety of noble metal composite materials, including single element or multi-element noble metals such as platinum, palladium, rhodium, iridium, and ruthenium.

[0026] (2) The method for preparing the noble metal / carbon nanosheet composite material of the present invention can realize the complete conversion of noble metal salt into metal nanoparticles. The noble metal ions are reduced by carbon to generate nanoparticles at high temperature. The conversion rate of the noble metal salt reaches 100%, thus avoiding the waste of the noble metal salt raw materials and achieving good economic efficiency.

[0027] (3) In the method for preparing the precious metal / carbon nanosheet composite material described in the present invention, the precious metal ions are directly pyrolyzed to obtain the precious metal / carbon nanosheet composite material, urea forms a graphite phase carbon nitride sheet structure material at 500-600°C, and polyvinyl pyrrolidone is pyrolyzed with the graphite phase carbon nitride nanosheet as a template to generate a sheet structure nitrogen-doped carbon material. The product does not require post-treatment and is environmentally friendly.

[0028] (4) The method for preparing the precious metal / carbon nanosheet composite material of the present invention is to directly obtain the precious metal / carbon nanosheet composite material by pyrolysis of polyvinyl pyrrolidone, urea and precious metal salt. The content of the precious metal component can be continuously adjusted, the metal content can reach more than 40wt%, and the precious metal loading is high.

[0029] (5) In the noble metal / carbon nanosheet composite material prepared by the method for preparing the noble metal / carbon nanosheet composite material described in the present invention, the noble metal nanoparticles are firmly bonded to the carbon nanosheets and are not easy to fall off during use, and the catalyst has a long service life.

[0030] (6) The raw materials used in the present invention are low in price and the preparation process is simple, which is conducive to industrial scale-up production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 TEM image of the ruthenium / carbon nanosheet composite material obtained in Example 1;

[0032] Figure 2 is the X-ray diffraction pattern of the ruthenium / carbon nanosheet composite material obtained in Example 2;

[0033] Figure 3 TEM image of the ruthenium / carbon nanosheet composite material obtained in Example 3;

[0034] Figure 4 TEM image of the iridium / carbon nanosheet composite material obtained in Example 4;

[0035] Figure 5 TEM image of the iridium / carbon nanosheet composite material obtained in Example 5;

[0036] Figure 6 This is the TEM image of the iridium / carbon nanosheet composite material obtained in Example 6. DETAILED DESCRIPTION

[0037] The above and other technical contents, features and effects of the present invention are described in detail below with reference to the attached Figure 1-6 The detailed description of the embodiments will clearly show that the structural contents mentioned in the following embodiments are all based on the drawings in the specification.

[0038] Example 1

[0039] A method for preparing a noble metal / carbon nanosheet composite material, comprising the following steps:

[0040] (1) 120 g of urea, 10 g of polyvinyl pyrrolidone and 2.0 g of ruthenium trichloride were mixed uniformly, heated to 200° C., stirred for 4 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under the protection of argon, the heating rate was controlled to be 4° C. / min, and the temperature was raised to 900° C., and after keeping the temperature for 2 h, the temperature was naturally cooled to room temperature to obtain a ruthenium / carbon nanosheet composite material, wherein the mass fraction of ruthenium in the obtained ruthenium / carbon nanosheet composite material was 20%.

[0041] Example 2

[0042] A method for preparing a noble metal / carbon nanosheet composite material, comprising the following steps:

[0043] (1) 100 g of urea, 8.0 g of polyvinyl pyrrolidone and 1.0 g of ruthenium trichloride were mixed uniformly, heated to 190° C., stirred for 2 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under nitrogen protection, the heating rate was controlled to be 10° C. / min, and the temperature was raised to 1000° C., and after keeping the temperature for 3 h, the temperature was naturally cooled to room temperature to obtain a ruthenium / carbon nanosheet composite material, and the mass fraction of ruthenium in the obtained ruthenium / carbon nanosheet composite material was 10%.

[0044] Example 3

[0045] A method for preparing a noble metal / carbon nanosheet composite material, comprising the following steps:

[0046] (1) 90 g of urea, 6 g of polyvinyl pyrrolidone and 0.4 g of ruthenium trichloride were mixed uniformly, heated to 230° C., stirred for 6 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under nitrogen protection, the heating rate was controlled to be 3° C. / min, and the temperature was raised to 900° C., and after keeping the temperature for 4 h, the temperature was naturally cooled to room temperature to obtain a ruthenium / carbon nanosheet composite material, and the mass fraction of ruthenium in the obtained ruthenium / carbon nanosheet composite material was 5%.

[0047] Example 4

[0048] A method for preparing a noble metal / carbon nanosheet composite material, comprising the following steps:

[0049] (1) 28 g of urea, 2.8 g of polyvinyl pyrrolidone and 0.4 g of iridium trichloride were mixed uniformly, heated to 220° C., stirred for 4 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under the protection of argon, the heating rate was controlled to be 5° C. / min, and the temperature was raised to 1000° C., and after keeping the temperature for 4 h, the temperature was naturally cooled to room temperature to obtain an iridium / carbon nanosheet composite material, wherein the mass fraction of iron in the obtained iridium / carbon nanosheet composite material was 40%.

[0050] Example 5

[0051] (1) 60g urea, 4.0g polyvinyl pyrrolidone and 0.4g iridium trichloride were mixed uniformly, heated to 180°C, stirred for 4h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under nitrogen protection, the heating rate was controlled to be 10°C / min, and the temperature was raised to 1000°C. After keeping the temperature for 1h, the temperature was naturally cooled to room temperature to obtain an iridium / carbon nanosheet composite material, and the mass fraction of iron in the obtained iridium / carbon nanosheet composite material was 10%.

[0052] Example 6

[0053] (1) 100 g of urea, 8 g of polyvinyl pyrrolidone and 0.4 g of tungsten hexachloride were mixed uniformly, heated to 160° C., stirred for 6 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under the protection of argon, the heating rate was controlled to be 8° C. / min, and the temperature was raised to 900° C. After keeping the temperature for 2 h, it was naturally cooled to room temperature to obtain an iridium / carbon nanosheet composite material, and the mass fraction of iron in the obtained iridium / carbon nanosheet composite material was 5%.

[0054] Example 7

[0055] (1) 45 g of urea, 3.0 g of polyvinyl pyrrolidone and 1.0 g of palladium acetylacetonate were mixed uniformly, heated to 220° C., stirred for 6 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under the protection of argon, the heating rate was controlled to be 1° C. / min, and the temperature was raised to 800° C., and after keeping the temperature for 2 h, the palladium / carbon nanosheet composite material was naturally cooled to room temperature, and the mass fraction of palladium in the obtained palladium / carbon nanosheet composite material was 5%.

[0056] Example 8

[0057] (1) 40 g of urea, 4 g of polyvinyl pyrrolidone and 0.4 g of platinum dichloride were mixed uniformly, heated to 240° C., stirred for 6 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under nitrogen protection, the heating rate was controlled to be 5° C. / min, and the temperature was raised to 800° C., and after keeping the temperature for 4 h, the temperature was naturally cooled to room temperature to obtain a platinum / carbon nanosheet composite material, and the mass fraction of platinum in the obtained platinum / carbon nanosheet composite material was 10%.

[0058] Example 9

[0059] (1) 40 g of urea, 3.0 g of polyvinyl pyrrolidone and 1.0 g of chloroplatinic acid hexahydrate were uniformly mixed, heated to 210° C., stirred for 4 h until completely solidified, and naturally cooled to room temperature to obtain a precursor; (2) The obtained precursor was placed in a tubular furnace, and under the protection of argon, the heating rate was controlled to be 3° C. / min, and the temperature was raised to 1000° C., and after keeping the temperature for 2 h, the temperature was naturally cooled to room temperature to obtain a platinum / carbon nanosheet composite material, and the mass fraction of platinum in the obtained platinum / carbon nanosheet composite material was 20%.

[0060] The above is a further detailed description of the present invention in combination with a specific implementation method, and it cannot be determined that the specific implementation of the present invention is limited to this; for technicians in the technical field to which the present invention belongs and related technical fields, the precious metal / carbon nanosheet composite material is prepared by adjusting the ratio to change the precious metal loading amount, changing the precious metal salt type, etc., but the technical principle is the same as that of the present invention, and the expansion, operation method, and data replacement should all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a noble metal / carbon nanosheet composite material, characterized in that: Prepared by the following steps: (1) After the noble metal salt, polyvinyl pyrrolidone and urea are uniformly mixed in a certain proportion, the mixture is heated and polymerized at 160-240° C. until the mixture is completely solid, and then naturally cooled to room temperature to obtain a precursor, wherein the heating time is 2-6 hours, the mass ratio of polyvinyl pyrrolidone to urea is 1:4-1:30, and the molar amount of the monomer in the polyvinyl pyrrolidone is more than 4 times that of the noble metal salt; (2) heating the precursor obtained in step (1) to 800-1000° C. for pyrolysis under programmed temperature control and non-oxidizing gas protection, with a heating rate of 1-10° C. / min and a pyrolysis time of 1-4 h, and then naturally cooling to room temperature to obtain a noble metal / carbon nanosheet composite material; The noble metal salt in step (1) is a platinum salt, a palladium salt, an iridium salt, a ruthenium salt or a rhodium salt.

2. The method for preparing the noble metal / carbon nanosheet composite material according to claim 1, characterized in that: The noble metal salt used in step (1) is one or more of noble metal acid salts, noble metal chlorides, noble metal nitrates, and noble metal acetylacetonate compounds.

3. The method for preparing the noble metal / carbon nanosheet composite material according to claim 1, characterized in that: The noble metal salt used in step (1) is one or more of chloroplatinic acid, platinum tetrachloride, platinum dichloride, platinum acetylacetonate, and platinum nitrate.

4. The method for preparing the noble metal / carbon nanosheet composite material according to claim 1, characterized in that: In the step (1), the mass ratio of polyvinyl pyrrolidone to urea is 1:5-1:20, and the molar amount of the monomer in polyvinyl pyrrolidone is more than 8-20 times that of the noble metal salt.

5. The method for preparing the noble metal / carbon nanosheet composite material according to claim 1, characterized in that: The non-oxidizing gas used in step (2) is one or a mixture of hydrogen, nitrogen, argon and helium.

6. The method for preparing the noble metal / carbon nanosheet composite material according to claim 1, characterized in that: The heating temperature in step (1) is 200-220° C., the programmed heating rate in step (2) is 3-5° C. / min, the pyrolysis time is 2 h, and the non-oxidizing gas is nitrogen.

7. A noble metal / carbon nanosheet composite material prepared according to the method for preparing a noble metal / carbon nanosheet composite material according to any one of claims 1 to 6.